Prevalence of asthma and respiratory symptoms among 15-17 year-old Cypriots in communities near power stations - Middleton, Nicos; Yiallouros, Panayiotis K.; Kolokotroni, Ourania; Koutrakis, Petros (My University, 2010)
BACKGROUND: Several studies have reported adverse effects of traffic pollution on respiratory health. Exposure to power plant emissions has not been as comprehensively studied.AIMS: This nationwide study investigated the association between responses of 6393 adolescents to the ISAAC questionnaire and proximity of their community to the three power plants in Cyprus.METHODS: Three outcomes were mapped: (i) active asthma (i.e. diagnosis with current respiratory symptoms), (ii) inactive asthma and (iii) respiratory symptoms in the absence of diagnosis. Evidence of increased morbidity in terms of proximity was assessed in logistic models after adjusting for other factors (e.g. smoking and co-morbidity).RESULTS: At 7.4%, prevalence of active asthma was elevated in communites near power stations but sharply reduced to the national levels of 5% at longer distances (p-value<0.06). Adjusted odds ratios among those residing within 5km (compared to 30km away) were 1.8 (95%CI:1.3,2.5) for active asthma and 0.8 (95%CI:0.6,0.9) for respiratory symtoms without diagnosis. No clear relationship was observed with inactive asthma. CONCLUSIONS: Risk of asthma appeared elevated near power stations, however, there was no evidence of a dose-response relationship. Furthermore, the lower frequency of symptoms without a diagnosis may indicate an excess of diagnoses in the presence of symptoms in these areas than elsewhere.
Keywords: Asthma; Respiratory symptoms; Air pollution